Intra And Extra-Oral Photograph For Orthodontic Records - Goenharto, Sianiwati (Record and Library Journal, 2016)
Orthodontic diagnosis and treatment plans are determined based of some analyzes that require data derived from direct examination, study models, x-rays and clinical photos. Currently the clinical photos both intra oral and extra oral are easily made. Unfortunately, not all clinicians are willing to make good documentation especially making photos, or making the inadequate ones. The purpose in this paper to reveal how to make good intra and extra-oral photos for orthodontic records as communication features between clinician and patients. Proper documentation is needed especially on orthodontic treatment that requires a relatively long period. There are at least 5 intra-oral photos that should be made: frontal photo, right and left buccal, upper and lower occlusal photos. Extra-oral photos are relatively easier made than intra-oral photos. The important thing is position of the patient and the clinician. Four extra-oral photos are face-frontal with lips relaxed and smiling, profile and 45o profile will provide the maximum information about the face, soft tissues, proportions and esthetic smile. All important details should be recorded. Photos before, during and after treatment can be compared to recognize the changes that have been achieved. Good orthodontic records includes intra and extra-oral photograph taking will minimize the misunderstandings between the dentist and the patients in orthodontic treatment.